2018
DOI: 10.1111/dmcn.14034
|View full text |Cite
|
Sign up to set email alerts
|

Age at referral for diagnosis and rehabilitation services for cerebral palsy: a scoping review

Abstract: Aim This study sought to: (1) determine what is known about age at referral for diagnosis and rehabilitation services for children suspected of having cerebral palsy (CP); and (2) identify factors associated with earlier referral. Method A scoping review was conducted to summarize existing literature. We systematically searched Allied and Complementary Medicine, CINAHL, Cochrane Library, Embase, and PsycINFO for evidence published between 1979 and 2017 on age at referral for diagnosis or age at referral to reh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 35 publications
3
28
0
Order By: Relevance
“…Foreign scholars have reported that in animal experiments, the position of the ACL tibial plateau on the tibial plateau was moved forward and backward, and the tibial plateau and knee stability were significantly different, suggesting the position of the tibial plateau and its restrictions [5]. e ability of the tibia to move forward and maintain the stability of the knee joint is closely related, but there is still no research report on the clear correspondence between the position of the ACL tibial stop and the ACL control force [6][7][8][9]. e connection point between the ligament and the bone is not a simple ligament bone connection, but a complex structure.…”
Section: Introductionmentioning
confidence: 99%
“…Foreign scholars have reported that in animal experiments, the position of the ACL tibial plateau on the tibial plateau was moved forward and backward, and the tibial plateau and knee stability were significantly different, suggesting the position of the tibial plateau and its restrictions [5]. e ability of the tibia to move forward and maintain the stability of the knee joint is closely related, but there is still no research report on the clear correspondence between the position of the ACL tibial stop and the ACL control force [6][7][8][9]. e connection point between the ligament and the bone is not a simple ligament bone connection, but a complex structure.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical diagnosis of unilateral CP may be considered a less optimal external criterion for investigating the predictive validity of the HAI because it is a symptomatic diagnosis; nonetheless, it is based on international classification 12 . The diagnosis of unilateral CP was collected from medical records at about 2 years of age and was not verified by an additional clinical examination at later age, which could have contributed to extremely mild cases being missed 26,27 . As for any other study investigating the sensitivity and specificity of a method, the retrieved estimates may to some extent have been overestimated because estimation and evaluation of the cut‐off values was performed in the same study sample, and need to be externally validated in another similar sample 28…”
Section: Discussionmentioning
confidence: 99%
“…The importance of early diagnosis and intervention for children with CP has been understood for decades [ 2 ]. Nonetheless, children with CP are still identified late [ 2 , 5 , 16 18 ], and studies investigating how CP manifests during infancy and what factors affect access to intervention have been called for [ 17 , 21 , 22 ]. By retrospectively reviewing medical charts, we aimed to describe clinical characteristics of infants with CP as well as what factors enable early access to physiotherapy.…”
Section: Introductionmentioning
confidence: 99%